Assessment of the functioning of the photosynthetic apparatus of Olea europaea L. under freezing temperatures - Sergei Yu. Tsiupka; Valentina A. Tsiupka; Ilya V. Bulavin (Siberian Journal of Life Sciences and Agriculture)
Background. Olive (O. europaea) is a popular fruit crop, and is the second in the world by area after coffee. The main limiting factor for olive cultivation in regions located on the northern border of the subtropical zone, as well as in temperate climates, is their low frost resistance. So, the aim of the present study was to evaluate the degree of influence of low negative temperatures on the functional state of leaves of different O. europaea genotypes.